Social and Psychological Factors in Bilingual Speech Production (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Studies in the fields of bilingualism and second language acquisition have shown that both cognitive and affective psychological factors can influence individuals’ bilingual speech production. More recently, both experimental and variationist studies of bilingual communities have examined the role of social factors on bilinguals’ speech, particularly in cases of long-term language contact and minority-language bilingualism. The Special Issue brings together work on the psychological and/or social factors that influence bilingual speech production as well as work that uses different methodological frameworks. We examine the role of such factors on bilingual speech production in diverse contexts, in order to provide a more holistic account of the ways in which extra-linguistic influences may affect bilinguals’ speech in one or both of their languages.